Nanocomposites: A Transparent, Wearable Fluorescent Mouthguard for High‐Sensitive Visualization and Accurate Localization of Hidden Dental Lesion Sites (Adv. Mater. 21/2020). Issue 21 (25th May 2020) - Li, Xuemeng; Luo, Chongdai; Fu, Quanying; Zhou, Cuiping; Ruelas, Marina; Wang, Yingshuting; He, Jinxu; Wang, Yangyang; Zhang, Yu Shrike; Zhou, Jianhua
Abstract : A unique approach for precisely locating dental lesion sites, including those hidden and often overlooked by dentists, is developed by Cuiping Zhou, Yu Shrike Zhang, Jianhua Zhou, and co‐workers, reported in article number 2000060, who use a fluorescent mouthguard consisting of a nanocomposite of zinc oxide and poly(dimethylsiloxane) to detect local release of volatile sulfur compounds. The low cost, long‐term stability, and good patient compliance of the mouthguard enable widely applicable, preliminary, yet accurate screening of dental lesions prior to dental clinics and routine physical examinations.